AC electrical properties of CNF/PTFE composite. (2023) - Uniyal, Divya; Ummer,; Juyal, Sakshi; Deep Singh, Gagan; Mishra, Abhilasha; Mohmmad, Noor; Kukreti, Ravish; Juneja, Pradeep; Singh Gill, Fateh
Abstract: In conductive nanocarbon-based polymer composite systems, carbon-nano-fibers (CNFs) provide good connectivity for electrical conduction due to their micrometer (μm) length compared to nano-meter (nm) length of carbon-nano-tubes (CNTs). However, an excellent electrical conductivity is demonstrated by the CNT compared to a CNF. This paper reports the AC electrical properties of CNF/PTFE composites prepared with partially coated CNF with PTFE. The sample structures were studied by means of Scanning Electron Microscopy (SEM). A negative capacitance (NC) has been observed in CNF/PTFE composites. The positive value of the imaginary part of impedance indicates the inductive nature of composites within applied frequencies (upto 1 MHz).